Tracking the ultrafast motion of an antiferromagnetic order parameter - Christian Tzschaschel (Nature Portfolio, 2019)
Understanding antiferromagnetic dynamics enables future information technologies, but the detection remains challenging. Here, the authors show the capability of tracking the three dimensional spin motions in YMnO3 by combining time resolved measurements of Faraday rotation and magneto-optical second harmonic generation.